What Are We to Understand Gracia to Mean? : Realist Challenges to Metaphysical Neutralism - Delfino, Robert A., (Value Inquiry Book Series ;, 2006)
This book provides a series of challenges to Jorge J. E. Gracia's views on metaphysics and categories made by realist philosophers in the Aristotelian and Thomistic traditions. Inclusion of Gracia's responses to his critics makes this book a useful companion to Gracia's Metaphysics and its Task: The Search for the Categorial Foundation of Knowledge.